No end of a lesson : Australia's unified national system of higher education - Macintyre, Stuart, 1947-2021; Brett, André; Croucher, Gwilym (Melbourne University Press, 2017)
A revolution swept through universities three decades ago, transforming them from elite institutions into a mass system of higher education. Teaching was aligned with occupational outcomes, research was directed to practical results. Campuses grew and universities became more entrepreneurial. Students had to juggle their study requirements with paid work, and were required to pay back part of the cost of their degrees. The federal government directed this transformation through the creation of a Unified National System. How did this happen? What were the gains and the losses? No End of a Lesson explores this radical reconstruction and assesses its consequences.